Stylised-facts view of fourth industrial revolution technologies impacting digital learning and workplace environments: ChatGPT and critical reflections - Chaka, Chaka (Frontiers in Education, 2023)
When the 21st century was ushered in, and in the period following its inception, there was a lot of hype about how 21st-centruty skills, especially the 4Cs (critical thinking, collaboration, communication and creativity), were going to play a pivotal role for digital learning and workplace environments. Two decades later, these environments are still grappling with the specific changes brought about and the actual role played by these skills in their respective facets. Within these two decades, though, a new hype has emerged about how fourth industrial revolution (4IR) technologies are likely to affect and change the future of digital learning and workplace environments in ways never seen in previous industrial and digital revolutions. Among these technologies, artificial intelligence and automation are touted as some of the technologies that will change the future of digital learning and work. Against this background, this paper sets out to critically reflect on the prospects and challenges these two 4IR technologies have for digital learning and work as the 21st century is on the cusp of the third decade. It does so by analysing and discussing AI-/machine-human fused stylised facts based on ChatGPT-generated responses and on a human distillation and reworking of those responses.